Psychological Predictors of Unhealthy Eating Attitudes in Young Adults - Izydorczyk, Bernadetta; Sitnik-Warchulska, Katarzyna; Lizińczyk, Sebastian; Lipiarz, Adrianna (Frontiers in Psychology, 2019)
The objective of this study was to determine the predictive role of psychological risk factors for restrained and compulsive eating in young women and men. We examined the relationship between resilience, impulsivity, emotional intelligence and self-esteem, and restrained and compulsive eating. It was assumed that resilience and impulsivity can directly explain unhealthy eating attitudes (restrained and compulsive: both emotional eating and external eating). The study group comprised 211 individuals (105 men and 106 women) aged 20-29, all of whom were living in southern Poland. Measures included the Resilience Measurement Scale (SPP-25), the Eysenck’s Impulsivity Inventory (IVE), the Multidimensional Self-Esteem Inventory (MSEI), the Emotional Intelligence Questionnaire (INTE), and the Polish adaptation of the Dutch Eating Behavior Questionnaire (DEBQ). The statistical analysis showed significant and positive correlations between emotional eating and general self-esteem, impulsivity, and weaker (but still significant) correlations with physical attractiveness. External eating was positively and significantly correlated with impulsivity and self-esteem (including physical attractiveness). Restrained eating was also positively and significantly correlated with general self-esteem. Both types of compulsive eating attitudes (emotional and external eating) were significantly and negatively correlated with resilience. Women showed a significantly higher positive correlation between impulsivity and external eating compared to men. The level of intensity of other measures proved similar across the entire study group regardless of sex. Impulsivity had the strongest and most direct significant influence on both emotional eating and external eating, and a negative effect on emotional intelligence. Resilience proved to have a significant impact on all three examined types of eating attitude (a direct negative effect on emotional eating and external eating, and positive direct effect on restrained eating), self-esteem, and emotional intelligence. An important psychological intervening variable in generating unhealthy eating attitudes proved to be self-esteem among both men and women. Emotional intelligence, which remains correlated with resilience, proved independent, with no effect on unhealthy eating attitudes. These results suggest that preventive treatment and educational programs implemented particularly among adolescents and young adults may support development of their psychological resources.